Concept and Structural Components of Social Skills (Baltic Journal of Sport and Health Sciences, 2012)
Research  background.  Though  a  variety  of  social  skill  explanations  exist,  in  essence  they  give  us  plenty examples  of  controversial  interpretation  of  social  skill  conception  and  classification.  So,  there  is  a  problem  of different semantic meanings in the concept of social skills and different classifications of them.Research aims were to reveal the multidimensionality of the construct of social skills and to create a theoretical model of their structure. Research method was theoretical analysis.Discussion and conclusions. After studying various explanations of social skills, we observed that not only a great variety of their interpretations was revealed, but also there is a problem of different semantic meaning: some authors named the same behavioral categories as social competences, others – as social skills, yet others – as social abilities, etc.  In addition, the authors present a variety of different classifications of social skill groups and the different structures of social skills. In this theoretical research we tried to analyze and systemize the explanations of social skills with reference to the data of scientific research from various countries. As a result of analysis and systemization of scientific data we offer a model of social skill structure and give interpretation  of  social  skill  concept  as  a  multidimensional  construct  created  from  integrative,  overlapping  and supplementing each other structural components of: 1) interaction skills; 2) communication skills; 3) participation skills; 4) emotional skills; and 5) social cognition skills. Each component of social skills is made up of certain behavioral abilities.Keywords: interaction skills; communication skills; participation skills; emotional skills; social cognition skills.